2014
DOI: 10.1111/jbi.12344
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of range expansion of white‐winged doves in the USA from 1979 to 2007

Abstract: Aim The geographical expansion of white-winged doves (Zenaida asiatica) in North America has attracted the attention of biologists and sportsmen because of their recreational and aesthetic value; however, data on factors driving the spatial spread of this species are lacking. We examined spatial and temporal patterns of range expansion for white-winged doves along the northern edge of their geographical range from 1979 to 2007 and used a dynamic occupancy model to estimate when and where doves would be found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…In bird distribution modelling, several studies have used dynamic occupancy modelling to study recent range dynamics (Kéry et al 2013, Butcher et al 2014, Yackulic et al 2015. Occupancy is described by colonisation and extinction processes (as in metapopulation models, Hanski 1998), which can be expressed as functions of environmental covariates (Kéry et al 2013).…”
Section: Multi-species Modelsmentioning
confidence: 99%
“…In bird distribution modelling, several studies have used dynamic occupancy modelling to study recent range dynamics (Kéry et al 2013, Butcher et al 2014, Yackulic et al 2015. Occupancy is described by colonisation and extinction processes (as in metapopulation models, Hanski 1998), which can be expressed as functions of environmental covariates (Kéry et al 2013).…”
Section: Multi-species Modelsmentioning
confidence: 99%
“…In general, our study shows the importance of understanding the contribution of habitat selection patterns to population expansion (Butcher et al., ; Veech et al., ). In particular, we showed that species can expand despite a relatively conservative nest site selection behavior, when changes in land use and human demographics provide new vacant areas open to colonization by the growing population (e.g., Balbontin, Negro, Sarasola, Ferrero, & Rivera, ; Cardador, Carrete, & Mañosa, ).…”
Section: Discussionmentioning
confidence: 69%
“…Puisqu'elle s'est avérée adaptée à la reconstitution de la dynamique invasive de l'ajonc à La Réunion, nous proposons d'inscrire cette méthode transdisciplinaire aux côtés de celles plus couramment utilisées en biologie pour répondre à ce genre de questions, à savoir les marqueurs moléculaires (Williams et al 2005, Guggisberg et al 2012, l'étude des parts d'herbier (ex : Delisle et al 2003, Chauvel et al 2006, Harris et al 2007, Lavoie et al 2007, Aikio et al 2010, les comparaisons cartographiques, d'échantillonnages ou d'inventaires (ex : Brunzel et al 2009, Butcher et al 2014. L'intérêt de multiplier les méthodes pour cerner l'histoire des processus invasifs est d'autant plus fort que chacune a ses limites : les marqueurs moléculaires ne sont pas utilisables sur toutes les espèces (et notamment pas sur l'ajonc à cette échelle de temps et d'espace, Hornoy 2012) et ne permettent pas d'atteindre une précision temporelle fine ; la compilation des parts d'herbiers souffre d'un biais lié à l'effort de collecte, variable selon les espaces et les époques (Delisle et al 2003, Chauvel et al 2006 ; les comparaisons de relevés et d'inventaires ne permettent que rarement de remonter au-delà de 30 à 40 ans.…”
Section: L'absence D'une Phase De Régressionunclassified